Recent advancements in liquid marbles: fabrication, materials, control mechanisms, and applications - Ghavami, Hamed; Liu, Yuxiang (Frontiers in Lab on a Chip Technologies, 2024)
Liquid marbles (LMs) are versatile soft matter systems comprising a liquid core encapsulated by a shell of hydrophobic particles. LMs exhibit non-wetting properties and hence have enhanced mobility compared with droplets on a solid substrate. Recent advances have expanded their fabrication methods, material choices, and applications, particularly in microfluidics. This mini-review highlights the progress in LM research over the past two years, focusing on novel fabrication techniques, unique materials, multi-physical control schemes, and emerging applications including solar energy harvesting, cell culture, controlled substance delivery, gas sensing, and pollutant decontamination. We provide opinions on the unaddressed needs in LM research and on the trend of LM developments, specifically for the applications of LMs in lab-on-a-chip applications.